THE EFFECT OF ECONOMIC LITERACY AND FINANCIAL INCLUSION ON CONSUMPTION BEHAVIOR MEDIATED BY RATIONAL CHOICE AMONG STUDENTS AT MAKASSAR STATE UNIVERSITY - Yunita Mahrany; Chalid Imran Musa; Inanna (RADJA PUBLIKA, 2026)
This study aims to examine the effect of economic literacy and financial inclusion on consumption behavior, with rational choice as a mediating variable among students at Makassar State University. The study employs a quantitative approach, with data collected through questionnaires distributed to students. Data analysis was conducted using SmartPLS software. The results indicate that economic literacy and financial inclusion have a positive and significant effect on both rational choice and consumption behavior directly. In addition, rational choice is proven to mediate the relationship between economic literacy and financial inclusion and consumption behavior, indicating that these two variables have a more optimal effect on consumption when students are able to make rational decisions. These findings emphasize the importance of improving economic literacy and expanding access to financial services as strategies for fostering more prudent and rational consumption behavior among students.